Le 'risorse' del metodo (ENTHYMEMA, 2020)
After introducing the main theme of the section “Italian Contemporary Poetry: methodological hypothesis and historiographical investigations”, this article calls into question long-established paradigms in the critical debate on poetry: the fragmentary nature of recent poetic production, and ideological disorientation. These topoi are often underpinned by a negative attitude towards pluralism and involve a nostalgic and one-dimensional conceptualization of tradition. By contrast, new routes for the historical and stylistic investigations of the poetic text may be opened thanks to the anti-essentialist concept of resource and a positive and adventurous idea of pluralism. The article then goes on to offer an overview of the first set of papers, which are mostly oriented towards theoretical and methodological innovation.
Keywords: contemporary Italian poetry; theoretical approaches to poetry; methodological debate; pluralism; theory of culture